White-eyed blowout fracture, child in danger: a case report - Rosli, Abdul Hadi; Nordin, Mohd-Hudzaifah; Embong, Zunaina; Wan Hitam, Wan-Hazabbah (Academy of Family Physicians of Malaysia, 2022)
A white-eyed blowout fracture is an orbital floor fracture associated with restriction of ocular motility (suggestive of orbital content entrapment) but with minimal or absence of signs of soft tissue trauma. It can lead to significant patient morbidity. This case involved an 8-year-old boy with a white-eyed blowout fracture following facial trauma. He presented with binocular diplopia and a history of recurrent episodes of vomiting after the trauma and was referred to our centre for a suspected head injury. Visual acuity in both eyes was 6/9 Examination showed minimal left periorbital haematoma with left eye motility restriction on superior and medial gaze associated with pain. CT scan of the orbit showed left orbital floor fracture with minimal soft tissue entrapment. He underwent urgent open exploration of the left orbit and release of orbital tissue entrapment. Post-operatively, the left eye motility restriction improved significantly with resolution of diplopia. In conclusion, a high index of suspicion is crucial in diagnosing paediatric white-eyed blowout fractures due to lack of external ocular signs.